The Importance of Tacit Knowledge: Dynamic Inventor Activity in the Commercialization Phase - Per Botolf Maurseth; Roger Svensson (Research Institute of Industrial Economics (IFN), 2020)
Inventors generally know more about their inventions than what is written down in patent applications. Because they possess this tacit knowledge, inventors may need to play an active role when patents are commercialized. We build on Arora (1995) and model firm-inventor cooperation in the commercialization of a given invention. Tacit knowledge warrants inventor activity. However, imperfect IPRs may reduce inventors' incentives to engage in the commercialization process. We analyze when first-best inventor activity is achieved in a two-stage contract. In the empirical part, we analyze when inventor activity is important for the successful commercialization of patents by using a detailed patent database. The database contains unique information on inventor activity, patent commercialization modes and the profitability of commercialization. In the empirical estimations, we find that inventor activity has a strong positive correlation with profitability when a patent is sold or licensed to another firm. When a patent is sold or licensed in the second phase, it is still inventor activity in the first phase that matters for profitability. Thus, our interpretation is that tacit knowledge and close cooperation between inventors and external firms are often crucial for the successful commercialization of patents.
Keywords: O31; O33; O34; 330; Tacit knowledge; Inventor activity; Patents; Commercialization